Ossifying renal tumor of infancy: a case report - Qu, Yu; Du, Guoqiang; Guo, Feng; Wu, Rongde; Liu, Wei (Frontiers in Oncology, 2023)
Ossifying renal tumor of infancy (ORTI) is an extremely rare benign renal solid tumor with typical clinical and pathological features. Most cases are diagnosed in infants less than 12 months of age, and more common in males. The first symptom in most patients is painless gross hematuria. Microscopically, the tumor has 3 main components: osteoid core, osteoblast-like cells and spindle cells. We reported a case of a 21-day-old patient diagnosed with ORTI who underwent partial nephrectomy and got good follow-up. The unique features of this case are strong expression of Wilms Tumor-1 (WT-1) and high Ki-67 index in the hot spot area. ORTI is considered to have a favorable prognosis. Due to the rarity of WT-1 positivity and high Ki-67 index, we should be highly aware that this patient needs to be followed closely. In addition, we reviewed the available literature on ORTI with the aim of summarizing the diagnostic and therapeutic experience. The diagnosis needs to be given cautiously on the basis of clinical symptoms, imaging and pathologic examination. Depending on the location and extent of the tumor, surgery can be performed by partial nephrectomy or nephrectomy to avoid overtreatment.